1992
DOI: 10.1172/jci115554
|View full text |Cite
|
Sign up to set email alerts
|

120-kD surface glycoprotein of Pneumocystis carinii is a ligand for surfactant protein A.

Abstract: Pneumocystis carinii is the most common cause oflife-threatening pneumonia in immunocompromised patients. In the current study, surfactant protein A (SP-A), the major nonserum protein constituent of pulmonary surfactant, is demonstrated to bind P. carinii in a specific and saturable manner. SP-A is surface bound and does not appear to be internalized or degraded by the P. carini organism. Furthermore, SP-A binding to P. carini' is time-and calcium-dependent and is competitively inhibited by mannosyl albumin. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(115 citation statements)
references
References 48 publications
5
108
2
Order By: Relevance
“…A number of recent in vitro studies have suggested that SP-A might be involved in pulmonary host-defence, and in phagocytosis in particular [11][12][13][14][15][16][17][18], and an interaction between SP-A and P. carinii has been demonstrated [20]. Preliminary studies suggest that although SP-A may stimulate the in vitro phagocytosis of some organisms [10,11,15], such as Candida albicans, Staphylococcus aureus and Herpes simplex, it may interfere with the phagocytosis of P. carinii by alveolar macrophages [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent in vitro studies have suggested that SP-A might be involved in pulmonary host-defence, and in phagocytosis in particular [11][12][13][14][15][16][17][18], and an interaction between SP-A and P. carinii has been demonstrated [20]. Preliminary studies suggest that although SP-A may stimulate the in vitro phagocytosis of some organisms [10,11,15], such as Candida albicans, Staphylococcus aureus and Herpes simplex, it may interfere with the phagocytosis of P. carinii by alveolar macrophages [10].…”
Section: Discussionmentioning
confidence: 99%
“…A number of striking similarities have been noted between SP-A and proteins involved in host defence in the alveolar lining layer. Interaction between SP-A and P. carinii has been demonstrated [20], and studies by our group suggest that this interaction interferes with the phagocytosis of P. carinii by alveolar macrophages ([10] -manuscript submitted). In the present study, we examined the production of SP-A messenger ribonucleic acid (mRNA) and protein in rats over time, in the presence and absence both of glucocorticoid-induced immunosuppression and infection with P. carinii.…”
mentioning
confidence: 99%
“…However, in addition to these properties, SP-A also has been shown to enhance the phagocytosis of bacteria and viruses by alveolar macrophages (Van Iwarden et al, 1991) and to induce the production of oxygen radicals by these cells. The binding of SP-A, via its lectin domain, has been shown to take place with the gp120 glycoprotein of Pneumocystis carinii (Zimmerman et al, 1992) and with Staphylococcus aureus (McNeely & Coon-rod, 1993), the latter binding enhancing the adherence of the SP-A coated bacteria to alveolar macrophages. SP-D is present at an approximately IO-fold lower level in the lung than SP-A, as judged by analysis of bronchoalveolar iavage.…”
Section: Binding Of the Collectins To Bacteria And Virusesmentioning
confidence: 99%
“…The collectins have been shown to bind to the surface of various micro-organisms and particles, and the critical discriminatory event in this process is the interaction of the Ctype lectin domain of the collectins and microbial carbohydrates [4][5][6][7][8][9]. One collectin, MBL, can enhance opsonization by activation of the classical pathway of complement in a Clq-and antibody-independent way [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%